2018
DOI: 10.1002/pro.3413
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for tankyrase‐RNF146 interaction reveals noncanonical tankyrase‐binding motifs

Abstract: Poly(ADP-ribosyl)ation (PARylation) catalyzed by the tankyrase enzymes (Tankyrase-1 and -2; a.k.a. PARP-5a and -5b) is involved in mitosis, telomere length regulation, GLUT-4 vesicle transport, and cell growth and differentiation. Together with the E3 ubiquitin ligase RNF146 (a.k.a. Iduna), tankyrases regulate the cellular levels of several important proteins including Axin, 3BP2, and angiomotins, which are key regulators of Wnt, Src and Hippo signaling, respectively. These tankyrase substrates are first PARyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
(163 reference statements)
2
31
0
Order By: Relevance
“…The Tankyrase-binding motif is a loosely conserved motif of RxxDG . The first and last amino acid (R1 and G6) in peptides or fragments that span the Tankyrase-binding motif of 3BP2, Axin1, RNF146 and IRAP abolish the interaction with Tnks-1/2 and are considered to be invariant amino acids (DaRosa et al, 2018;Morrone et al, 2012;. Mutation analysis of a peptide spanning the TBD of 3BP2 demonstrated that at position 4, glycine, proline, alanine and cysteine are preferred while isoleucine, leucine and valine prevent Tnks-1/2 binding to the 3BP2 peptide ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tankyrase-binding motif is a loosely conserved motif of RxxDG . The first and last amino acid (R1 and G6) in peptides or fragments that span the Tankyrase-binding motif of 3BP2, Axin1, RNF146 and IRAP abolish the interaction with Tnks-1/2 and are considered to be invariant amino acids (DaRosa et al, 2018;Morrone et al, 2012;. Mutation analysis of a peptide spanning the TBD of 3BP2 demonstrated that at position 4, glycine, proline, alanine and cysteine are preferred while isoleucine, leucine and valine prevent Tnks-1/2 binding to the 3BP2 peptide ).…”
Section: Discussionmentioning
confidence: 99%
“…Tnks-1/2 both have a PARP domain, a sterile alpha motif (SAM) and 5 Ankyrin-repeat clusters (ARCs) (Citarelli et al, 2010). The SAM domain mediates self-polymerization of Tnks-1/2, which is a biophysical property required for Tnks-1/2 function (De Rycker and Price, 2004;De Rycker et al, 2003;Mariotti et al, 2016).The ARCs bind to a loosely conserved Tankyrase-binding motif (TBM) -RxxDG, where x represents any amino acid and  is a small hydrophobic amino acid or glycine -that is embedded in target proteins (DaRosa et al, 2018;Morrone et al, 2012;. A central role of Tnks-1/2 is in protein turnover by the UPS (Bhardwaj et al, 2017;Chang et al, 2003;Cho-Park and Steller, 2013;Huang et al, 2009;Levaot et al, 2011;Li et al, 2017b;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported in 2011 and 2012 first revealed the structural basis of substrate recruitment by tankyrase (Guettler et al 2011 ; Morrone et al 2012 ). To date, numerous additional crystal structures of tankyrase ARCs from both TNKS and TNKS2, typically complexed with TBM peptides, are available (Li et al 2016 ; Eisemann et al 2016 ; Xu et al 2017a , b ; DaRosa et al 2018 ).…”
Section: Biological Contextmentioning
confidence: 99%
“…Additional contacts are provided by residues at TBM positions 4 and 5, which interact with a ‘central patch’ in the peptide-binding pocket, and at TBM position 8, where an acidic residue can confer increased binding affinity through a salt bridge (Guettler et al 2011 ). The eight amino acids of the TBM do not need to be contiguous: the essential arginine can be N-terminally displaced to varying extent, and structural plasticity or looping of such TBM peptides enables both the arginine and a hydrophobic side chain at position 4 to dock as in “canonical” TBM peptides (Morrone et al 2012 ; DaRosa et al 2018 ). Moreover, there is evidence for tankyrase targets devoid of detectable TBM sequences (Li et al 2017 ; Bhardwaj et al 2017 ).…”
Section: Biological Contextmentioning
confidence: 99%
“…The PAR ligand allosterically activates the E3 ligase through a conformational change in the N-terminal RING domain to promote K48-ubiquitination of its targets (DaRosa et al 2015). RNF146 can also bind to the ARC domains in tankyrase 1 or tankyrase 2 directly through motifs in its C terminus, thereby favoring PARylated tankyrases and their bound PARylated targets for ubiquitination and degradation (DaRosa et al 2015(DaRosa et al , 2018. In this way, tankyrases regulate the cellular levels of several disease-related cytoplasmic proteins including Axin, 3BP2, PTEN, and the angiomotins, which are key regulators of the Wnt/β-catenin, SRC, AKT, and Hippo signaling pathways, respectively (Huang et al 2009;Levaot et al 2011;Li et al 2015;Wang et al 2015).…”
Section: Par-binding Modules In Protein Degradationmentioning
confidence: 99%